2019
DOI: 10.1137/17m1142107
|View full text |Cite
|
Sign up to set email alerts
|

Obligate Mutualism in a Resource-Based Framework

Abstract: Obligate mutualist interactions appear to be ubiquitous in nature but cannot be described by the simple models that have been so effective for developing the theory of other population interactions including competition, predation, mixotrophy, and facultative mutualism. We present a teaching framework that extends the standard Lotka-Volterra analysis of these interactions to the more complicated obligate mutualism. This provides a useful addition to applications of dynamical systems theory for mathematics stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…, is equivalent to the classic fail diagram of Lotka-Volterra models of obligate mutualism (Figure 1(a)). We emphasise this similarity in Figure 4 The reasons for this are explained in detail in [30].…”
Section: Dynamical Properties Of the Obligate Mutualist Modelmentioning
confidence: 81%
See 1 more Smart Citation
“…, is equivalent to the classic fail diagram of Lotka-Volterra models of obligate mutualism (Figure 1(a)). We emphasise this similarity in Figure 4 The reasons for this are explained in detail in [30].…”
Section: Dynamical Properties Of the Obligate Mutualist Modelmentioning
confidence: 81%
“…Our results show that it essentially the abstraction of a resource as a carrying capacity, that constrains a three-dimensional problem to two dimensions, that is the cause of the problem. In previous work, we showed that particular mutualist processes such as plant-pollinator interactions and mutualist autotrophs can be successfully modelled in this framework [30] . Loreau [31] suggests that Lotka-Volterra models are unable to produce useful answers for obligate mutualism because they ignore fundamental mass-balance constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionary bounds may stem from physical considerations such as maximum or minimum body size, as Kempes et al [25] suggest, environmental tolerances, or population traits that, for example, may limit mutualism benefits as Cropp and Norbury [11,13] have shown theoretically. The use of a bounded trait distribution such as a beta distribution has the advantage of allowing phenotypes to explore the bounds of a trait, and for eco-evolutionary equilibrium points at the bounds to potentially provide useful information on the eco-evolutionary system dynamics.…”
Section: Introductionmentioning
confidence: 99%